Woody debris is related to reach‐scale hotspots of lowland stream ecosystem respiration under baseflow conditions. Issue 5 (23rd March 2018) - Blaen, P.J.; Kurz, M.J.; Drummond, J.D.; Knapp, J.L.A.; Mendoza‐Lera, C.; Schmadel, N.M.; Klaar, M.J.; Jäger, A.; Folegot, S.; Lee‐Cullin, J.; Ward, A.S.; Zarnetske, J.P.; et al.
Abstract: Stream metabolism is a fundamental, integrative indicator of aquatic ecosystem functioning. However, it is not well understood how heterogeneity in physical channel form, particularly in relation to and caused by in‐stream woody debris, regulates stream metabolism in lowland streams. We combined conservative and reactive stream tracers to investigate relationships between patterns in stream channel morphology and hydrological transport ( form ) and metabolic processes as characterized by ecosystem respiration ( function ) in a forested lowland stream at baseflow. Stream reach‐scale ecosystem respiration was related to locations ("hotspots") with a high abundance of woody debris. In contrast, nearly all other measured hydrological and geomorphic variables previously documented or hypothesized to influence stream metabolism did not significantly explain ecosystem respiration. Our results suggest the existence of key differences in physical controls on ecosystem respiration between lowland stream systems (this study) and smaller upland streams (most previous studies) under baseflow conditions. As such, these findings have implications for reactive transport models that predict biogeochemical transformation rates from hydraulic transport parameters, for upscaling frameworks that represent biological stream processes at larger network scales, and for the effective management and restoration of aquatic ecosystems.